Readability of online information about HPV Immunization - Sarah A. MacLean; Corey H. Basch; Danna Ethan; Phillip Garcia (Human Vaccines & Immunotherapeutics, 2019)
The human papillomavirus (HPV) vaccine is highly effective in preventing anogenital cancers, but vaccination rates in the United States remain low. In deciding whether to vaccinate their children, parents are increasingly using the internet to gather information. This study aimed to examine the level of readability of information on HPV vaccines written on 100 websites that were found via an internet search. To create the website sample, the first 50 websites from the search “HPV immunization” were recorded, followed by the first 50 non-duplicated websites from the search “Gardasil.” The content of the sites was analyzed using established readability scales. Websites were compared based on keyword search and on whether they had a commercial or non-commercial URL extension. The majority of websites were found to have information of a difficult reading level. Websites with commercial URL extensions and websites found using the search “Gardasil” had higher mean readability scores. These results suggest that many parents may not understand the information currently presented on the internet and that interventions aimed at improving the readability of online information could help to increase parental approval of the vaccine.